2019
DOI: 10.4103/aer.aer_116_19
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of sub-Tenon's block with levobupivacaine in retinal surgery under general anesthesia

Abstract: Background:Vitreoretinal surgery is associated with undesirable intraoperative and postoperative complications including pain, postoperative nausea and vomiting, and oculocardiac reflex (OCR). Systemic analgesics have side effects and are contraindicated in some cases. We hypothesized that the preoperative sub-Tenon's injection of levobupivacaine with general anesthesia would decrease postoperative pain and intraocular pressure as well as the incidence of complication.Methods:Eighty patients who were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…Asmer et al [ 47 ], who achieved OCR incidence rates in similar groups to the current study, observed that the combination of GA and sub-Tenon’s block, using levobupivacaine in retinal surgery patients, decreases the incidence of OCR to 3 cases out of 40, as compared to that of general anesthesia alone, which decreases OCR incidence to 6 cases out of 40 [ 43 ]. No statistically significant differences were observed between groups in the current study, so even AoA guidance for GA eliminated the hypothetical benefit of PA using different techniques, especially regional anesthesia techniques (PBB, TA), which were reported to reduce the incidence of OCR in the literature.…”
Section: Discussionsupporting
confidence: 74%
“…Asmer et al [ 47 ], who achieved OCR incidence rates in similar groups to the current study, observed that the combination of GA and sub-Tenon’s block, using levobupivacaine in retinal surgery patients, decreases the incidence of OCR to 3 cases out of 40, as compared to that of general anesthesia alone, which decreases OCR incidence to 6 cases out of 40 [ 43 ]. No statistically significant differences were observed between groups in the current study, so even AoA guidance for GA eliminated the hypothetical benefit of PA using different techniques, especially regional anesthesia techniques (PBB, TA), which were reported to reduce the incidence of OCR in the literature.…”
Section: Discussionsupporting
confidence: 74%
“…VRC, genel anestezi altında yapılan en yaygın oftalmik prosedürlerden biridir. 20 İndüksiyon ve idame için intravenöz ve volatil anestezik ajanlar, opioidler ve nöromüsküler bloke edici ajanların göz içi basıncını (GİB)›i yaklaşık %30 oranında azalttığı akılda tutulmalıdır. 21 Hava yolu yönetimi için laringoskopi kullanımı ise genellikle sempatik yanıttan kaynaklanan GİB artışına yol açmaktadır.…”
Section: Resim 1: Retrobulber Kanül Kullanılarak Glob Ve Infraorbital...unclassified
“…O ver the years, vitreoretinal surgery has been performed under different forms of anesthesia. [1][2][3][4] General and regional anesthetic techniques, including topical, 5 retrobulbar, 6,7 peribulbar, 6,8 and sub-Tenon blocks, [9][10][11][12][13][14] have been widely used to provide akinesia and analgesia. 15 Nowadays, anesthesia for vitreoretinal surgery is still challenging.…”
mentioning
confidence: 99%
“…This surgery is typically longer than routine ophthalmic surgery, and patients frequently suffer from systemic diseases such as diabetes, 16,17 which may interfere with the pain experience. Although vitreoretinal surgery is one of the most common ophthalmic procedures performed under general anesthesia, 4 peribulbar block (PB) and sub-Tenon's injection (STI) are most widely used. 2 Sub-Tenon's anesthesia was first described by Turnbull and later revisited by Stevens in 1992.…”
mentioning
confidence: 99%